Changes in the Porcine Intestinal Microbiome in Response to Infection with Salmonella enterica and Lawsonia intracellularis. - Klaudyna A Borewicz; Hyeun Bum Kim; Randall S Singer; Connie J Gebhart; Srinand Sreevatsan; Timothy Johnson; Richard E Isaacson (PLoS ONE, 2015)
Salmonella enterica is a leading cause of food borne illness. Recent studies have shown that S. enterica is a pathogen capable of causing alterations to the composition of the intestinal microbiome. A recent prospective study of French pork production farms found a statistically significant association between Lawsonia intracellularis and carriage of S. enterica. In the current study the composition of the gut microbiome was determined in pigs challenged with S. enterica serovar Typhimurium and or L. intracellularis and compared to non-challenged control pigs. Principal coordinate analysis demonstrated that there was a disruption in the composition of the gut microbiome in the colon and cecum of pigs challenged with either pathogen. The compositions of the microbiomes of challenged pigs were similar to each other but differed from the non-challenged controls. There also were statistically significant increases in Anaerobacter, Barnesiella, Pediococcus, Sporacetigenium, Turicibacter, Catenibacterium, Prevotella, Pseudobutyrivibrio, and Xylanibacter in the challenged pigs. To determine if these changes were specific to experimentally challenged pigs, we determined the compositions of the fecal microbiomes of naturally infected pigs that were carriers of S. enterica. Pigs that were frequent shedders of S. enterica were shown to have similar fecal microbiomes compared to non-shedders or pigs that shed S. enterica infrequently. In a comparison of the differentially abundant bacteria in the naturally infected pigs compared to experimentally challenged pigs, 9 genera were differentially abundant and each exhibited the same increase or decrease in abundance between the two groups. Thus, there were similar changes in the GI microbiome associated with carriage of S. enterica regardless of whether the pigs were experimentally challenged with S. enterica or acquired it naturally.